Kajian Kesesuaian Parameter Kualitas Air Mineral Pada Produk Kemasan Di Desa Sumber Sari Kecamatan Moramo - Tryantini Sundi Putri Sundi; Ranno Marlany Rachman; Anafi Minmahddun; Romy Talanipa; Muh. Dirham (Jurusan Teknik Sipil, Universitas Halu Oleo, 2024)
The monitoring of drinking water quality across all districts/cities, both internally and externally, is part of monitoring the health impacts on the community and improving the drinking water supply system, as well as enhancing the community's capacity to care for obtaining safe water quality. The aim of this study is to determine the comparison of water quality before and after processing into drinking water, based on physical, chemical, and biological parameters, specifically focusing on CLEO packaged products in Sumber Sari village, Moramo district, in accordance with the standard quality regulations for drinking water stipulated in Minister of Health Regulation No. 2 of 2023. Data collection was conducted through observation and analytical testing methods. Water samples were taken from the service reservoir tank, using the immersion method (dip sampling) as the sampling technique. The research findings indicate that both before and after processing Cleo packaged drinking water, in terms of physical, chemical, and microbiological parameters, exhibit different maximum parameter values but still meet the standard quality requirements.